PENGARUH DOSIS DOLOMIT DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANGMERAH(Alium ascalanicum L) VARIETAS VIETNAM - Manurung, Agnes I.; Vindo, Vindo (JURNAL AGROTEKDA; Vol 3 No 2 (2019): SEPTEMBER, 2020)
This study aims at obtaining the correct dose of dolomite and KCl fertilizer on the growth and yield of Vietnamese varieties of shallots (Allium ascalonicum L.). The research was conducted at Jl. Binjai km. 10.8, namely the Experimental Field at the Faculty of Agriculture, Darma Agung University, Medan Binjai District with a height of  ±  28 m above sea level, starting from June to September 2016. This research used a factorial randomized block design (RBD) with two factors. Treatment namely dose of dolomite and KCl fertilizer. Factor I is Dolomite (D) dose which consists of 4 (four) levels, namely: D0 = control, D1 = 1.5 ton / ha (150 g / plot), D2 = 3.0 ton / ha (300 g / plot), D3 = 4.5 ton / ha (450 g / plot). Factor II is The dose of potassium (K) fertilizer with 3 (three) treatment levels, namely: K0 = control, K1 = 100 kg / ha (10 g / plot), K2 = 200 kg / ha (20 g / plot). The results showed that, giving a dose of 450 g dolomite / plot can increase plant height, number of tillers, number of leaves, leaf length, tuber diameter, tuber wet weight per sample, tuber dry weight per sample and tuber dry weight per plot linearly, but it has no effect on tuber wet weight per plot. Application of potassium fertilizer up to a dose of 20 g / plot can increase plant height, number of tillers, number of leaves, length of leaves, tuber diameter, tuber wet weight per sample, tuber dry weight per sample and tuber dry weight per plot linearly, but it affects the weight wet tubers per plot. The interaction of dolomite and potassium fertilizer has no significantly effect on all observed parameters.